Efectos de la migración parental en el estado emocional de los estudiantes de bachillerato de la Unidad Educativa Ciudad de Valencia - Burgos Chaguay, Ana Doménica (2025)
Through this work we analyze the effects of parental migration on the emotional state of high school students at the Ciudad de Valencia Educational Unit. The absence of parental figures generates feelings of sadness, anxiety and stress. This situation has a direct impact on the academic performance and emotional development of adolescents. It is a descriptive cross-sectional study, of a mixed nature. The population under study was made up of children of migrant parents; questionnaires and observation forms were used. The selected sample was of convenience, meeting the inclusion and exclusion criteria, as well as the ethical principles of the research. The results indicate the need to implement emotional and academic support programs for these young people. Furthermore, the advantages of using ICTs as a tool to maintain emotional ties between migrant parents are highlighted.